Simultaneous development of pneumonitis and autoimmune diabetes secondary to immune checkpoint inhibitor treatment with durvalumab in an advanced small cell lung cancer patient: A case report. Issue 48 (2nd December 2022) - Wen, Yan-Ping; Xiao, Hai-Wei; Yin, Ju-Hua; Guo, Hui-Ru; Shan, Meng-Jun; Shen, Li-Ping; Liu, Ling-Shuang
Abstract : Rationale: Immune checkpoint inhibitors (ICIs) have been widely used in the treatment of various types of cancers worldwide, which is the most significant breakthrough in cancer therapy in recent years. Despite their excellent benefits in anti-tumor efficacy, a subset of patients will experience various autoimmune toxicities, termed as immune-related adverse events (irAEs), which can affect almost any organ systems, but related to the pulmonary and pancreatic islets simultaneously has rarely been reported and discussed. Patient concerns: In this report, we describe a rare case of a 65-year-old man patient with advanced small cell lung cancer (SCLC) who suffered general fatigue, dry cough, chest tightness, shortness of breath and polyuria-polydipsia syndrome after the eighth cycle treatment with programmed cell death ligand-1 (PD-L1) inhibitor durvalumab. Diagnoses: According to the results of laboratory tests, chest computed tomography and multidisciplinary discussion, the patient was eventually diagnosed with ICI-related pneumonitis and autoimmune diabetes mellitus. Interventions: Multiple daily subcutaneous insulin injections, empirical anti-infection and immunosuppression treatment with corticosteroids were performed. Outcomes: After the cessation of durvalumab and comprehensive treatment, the patient's respiratory condition was relieved significantly and his blood glucose was well controlled with insulin therapy. Lessons: With the widespread use of ICIs, there will be more patients developing these rare but severe irAEs in clinical practice, which should attract great attention of both clinicians and patients.